2009
DOI: 10.1111/j.1365-2842.2008.01924.x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective food intake ability in relation to maximal bite force among Korean adults

Abstract: This study examined the relationship between the subjective food intake of 30 food types and their objective bite force to identify the key food items within the 30 food types to achieve a greater depth of masticatory function in Korean adults. A sample of 308 (112 males and 196 females) adults over the age of 20 (average age, 48.6) was selected among patients who visited four dental hospitals in Seoul, Korea. The subjective masticatory ability was evaluated through an interview with food intake ability questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 24 publications
5
68
1
Order By: Relevance
“…Pandis and Eliades 31 interpreted the differences in failure rates and contradictory evidence from studies testing identical materials in different populations to mean that culturally influenced dietary habits also affect the failure rate of brackets in vivo. Many popular Korean foods are relatively hard foods 32 (white radish kimchi, parched anchovies, dried filefish, etc). Differences in patient compliance with instructions regarding avoidance of such hard foods may also account for this difference in failure rate.…”
Section: Survival Analysis Of Brackets and Tubesmentioning
confidence: 99%
“…Pandis and Eliades 31 interpreted the differences in failure rates and contradictory evidence from studies testing identical materials in different populations to mean that culturally influenced dietary habits also affect the failure rate of brackets in vivo. Many popular Korean foods are relatively hard foods 32 (white radish kimchi, parched anchovies, dried filefish, etc). Differences in patient compliance with instructions regarding avoidance of such hard foods may also account for this difference in failure rate.…”
Section: Survival Analysis Of Brackets and Tubesmentioning
confidence: 99%
“…Correlation test between the VAS, FIA and MAI was not conducted in this study, but other studies on masticatory function have shown the moderate correlation of VAS and MAI, FIA and MAI. 15,35) Compare the M-T group with the M group, the VAS, FIA and MAI decreased much more in M-T group. The difference between two groups was evident at 4 weeks, and it was statistically significant in the VAS and FIA, but not in the MAI.…”
Section: ) Mixing Ability Index (Mai)mentioning
confidence: 99%
“…33) Based on the Sugihara et al, Kim et al developed new FIA questionnaire composed of 30 types of Korean foods and applied it on Korean adults. 15,16) But, there's no study on relation to the botulinum toxin injection.…”
Section: ) Mixing Ability Index (Mai)mentioning
confidence: 99%
See 2 more Smart Citations